The Responses of Light Reaction of Photosynthesis to Dynamic Sunflecks in a Typically Shade-Tolerant Species Panax notoginseng - Zhang, Jin-Yan; Zhang, Qiang-Hao; Shuang, Sheng-Pu; Cun, Zhu; Wu, Hong-Min; Chen, Jun-Wen (Frontiers in Plant Science, 2021)
Light is highly heterogeneous in natural conditions, and plants need to evolve a series of strategies to acclimate the dynamic light since it is immobile. The present study aimed to elucidate the response of light reaction of photosynthesis to dynamic sunflecks in a shade-tolerant species Panax notoginseng and to examine the regulatory mechanisms involved in an adaptation to the simulated sunflecks. When P. notoginseng was exposed to the simulated sunflecks, non-photochemical quenching (NPQ) increased rapidly to the maximum value. Moreover, in response to the simulated sunflecks, there was a rapid increase in light-dependent heat dissipation quantum efficiency of photosystem II (PSII) (ΦNPQ), while the maximum quantum yield of PSII under light (Fv′/Fm′) declined. The relatively high fluorescence and constitutive heat dissipation quantum efficiency of PSII (Φf,d) in the plants exposed to transient high light (400, 800, and 1,600 μmol m–2 s–1) was accompanied by the low effective photochemical quantum yield of PSII (ΦPSII) after the dark recovery for 15 min, whereas the plants exposed to transient low light (50 μmol m–2 s–1) has been shown to lead to significant elevation in ΦPSII after darkness recovery. Furthermore, PSII fluorescence and constitutive heat dissipation electron transfer rate (Jf,d) was increased with the intensity of the simulated sunflecks, the residual absorbed energy used for the non-net carboxylative processes (JNC) was decreased when the response of electron transfer rate of NPQ pathway of PSII (JNPQ) to transient low light is restricted. In addition, the acceptor-side limitation of PSI [Y(NA)] was increased, while the donor-side limitation of photosystems I (PSI) [Y(ND)] was decreased at transient high light conditions accompanied with active cyclic electron flow (CEF). Meanwhile, when the leaves were exposed to transient high light, the xanthophyll cycle (V cycle) was activated and subsequently, the JNPQ began to increase. The de-epoxidation state [(Z + A)/(V + A + Z)] was strongly correlated with NPQ in response to the sunflecks. In the present study, a rapid engagement of lutein epoxide (Lx) after the low intensity of sunfleck together with the lower NPQ contributed to an elevation in the maximum photochemical quantum efficiency of PSII under the light. The analysis based on the correlation between the CEF and electron flow devoted to Ribulose-1, 5-bisphosphate (RuBP) oxygenation (JO) indicated that at a high light intensity of sunflecks, the electron flow largely devoted to RuBP oxygenation would contribute to the operation of the CEF. Overall, photorespiration plays an important role in regulating the CEF of the shade-tolerant species, such as P. notoginseng in response to transient high light, whereas active Lx cycle together with the decelerated NPQ may be an effective mechanism of elevating the maximum photochemical quantum efficiency of PSII under light exposure to transient low light.